The Effects of Different Patterns of Tooth Agenesis on Tooth Dimensions - Ceyhan, Derya; Kirzioglu, Zuhal (Journal of Dentistry Indonesia, 2018)
Objective: Tooth agenesis is a multifactorial condition accompanied by morphological differences. This study aimed to investigate the effects of different patterns of tooth agenesis on tooth dimensions. Methods: Records of children registered at the Department of Pedodontics and had tooth agenesis were reviewed, and those aged between 7 and 18 years of age with no systemic diseases, syndromes, or fluorosis were included in the study; the third molars were excluded. The study sample comprised 82 patients with one to six teeth missing (Group 1; hypodontia), 26 with more than six teeth missing (Group 2; oligodontia), and 31 with no missing teeth (Group 3; control). Mesiodistal widths, buccopalatal/labiolingual depths, and cervicoincisal/cervicoocclusal heights of permanent teeth were measured. Data were analyzed statistically. Results: Majority of the teeth in Group 2 were smaller than those in the other groups. Tooth agenesis was correlated with a dimensional decrease in mesiodistal width. Tooth dimensions were generally smaller in patients with tooth agenesis in both jaws (upper and lower) and regions (anterior and posterior). Conclusion: Decrease in tooth dimensions increased with the increase in the number of missing teeth. Teeth with clinically reduced dimensions or modifications during formation should receive additional attention from clinicians with regard to tooth agenesis.